THE GROWING PERSPECTIVES OF CURLY BEAN UNDER PODILYA CONDITIONS - Дудчак, Т. В.; Вільчинська, Д. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
In connection with the opening ceremony of the International Year of legumes in 2016 analyzing the problems that covers this event offers new varieties of beans winding Multiflora (Phaseolus multiflorus Wild) and the feasibility of its cultivation on the tail. It was made the detailed description of morphological traits on the contrast, uniformity and stability of the individual organs of plants "Sokilchanka" varieties and "Dnistrovka". This bean cultivation technology involves the use of plants’many-support systems. In the absence of such support means shortage of the crop reaches 50% or more, therefore analyzed different designs that have been used to support the plant, on the basis of theseresearches the optimal harness for climbing beans forms, and its testing carried out by the State Department of Intellectual Property Ministry of Education of Ukraine. These results of phenological observations, which are the technological landmarks timely planting, agro-holding for the care of plants, determining the best timing of harvesting, as a method for growing beans winding does not provide for mechanical harvesting.The Recommended technological complex of growing beans winding for farms and gardens is an agro-ecological, with a yield of up to 5 t / ha.